Význam adrenalinového autoinjektoru - Herknerová, Madgalena (Medicína pro praxi, 2023)
Adrenaline delivery via adrenaline autoinjectors represents a rapid and life-saving first-line treatment of anaphylaxis. Adrenaline administration via autoinjector results in the more rapid achievement of peak systemic delivery of adrenaline. This paper brings data about adrenaline autoinjector prescription based on the optimal diagnostics (example of component resolved diagnostics in food-induced anaphylaxis) and the adequate usage of adrenaline autoinjector.
Keywords: Anaphylaxis; potravinová alergie; autoinjektor; rizikové faktory; Self Administration; Food Hypersensitivity; adrenalin; Humans; lidé; anafylaxe; Risk Factors; Epinephrine; autoaplikace